2000
DOI: 10.1046/j.1523-1747.2000.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Mast Cell Chymase and Tryptase and of c-Kit in Human Cutaneous Scar Tissue

Abstract: In order to explore a possible involvement of mast cells during human wound healing, we studied sections from scars (4-369-d-old) (N = 20) and normal skin (N = 10) for mast-cell-specific tryptase and chymase by enzyme histochemistry, for the stem cell factor receptor c-Kit and the melanosomal marker TA99 by immunohistochemistry, and for simultaneous c-Kit expression and avidin fluorescence by double staining. Enzyme activities and mRNA expression were also studied in tissue extracts. Chymase-reactive mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 43 publications
8
42
0
1
Order By: Relevance
“…In the formation stage of hypertrophic scars, an increase in the mast cell number is positively correlated with the severity of fibrosis (17). Compared with normal skin, active transmitters associated with mast cells are significantly increased, suggesting that mast cells and their transmitters are key factors for promoting hypertrophic scar formation (17). Chymase secreted by mast cells participates in the formation of skin matrix (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In the formation stage of hypertrophic scars, an increase in the mast cell number is positively correlated with the severity of fibrosis (17). Compared with normal skin, active transmitters associated with mast cells are significantly increased, suggesting that mast cells and their transmitters are key factors for promoting hypertrophic scar formation (17). Chymase secreted by mast cells participates in the formation of skin matrix (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In human cutaneous wound healing, enzyme histochemical staining studies revealed that the number of chymase-positive mast cells decreased at various points after wounding, but that of tryptase-positive mast cells was either unchanged or increased [14][15][16]. According to Hermes et al [17], both chymase activity and its mRNA expression decreased in human scar extracts, whereas those of tryptase increased between day 23 and day 56 after wounding. Thus, it could be speculated that the tryptase-positive and chymase-negative mast cells appear during cutaneous wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are found in both internal fibrotic lesions and sites of wound healing (3537). Mast cells degranulate in response to external stimuli (37) to release, among other things, the protease tryptase (3739).…”
Section: Introductionmentioning
confidence: 99%